Creation Care in Genesis 1–2: An African Biblical-Ethical, Religious Perspectives - Udoekpo, Michael Ufok (Sekolah Tinggi Teologi Injili Indonesia Samarinda, 2026)
This article examines Genesis 1–2 through an African biblical-ethical lens, arguing that the creation narratives provide a theological foundation for ecological responsibility within African religious contexts. It contends that African ecological consciousness is deeply embedded in religious ethics, communal values, and the lived experience of interdependence between human beings, the natural world, and God as Creator. Using a contextual-critical method, the study engages Genesis 1–2 in dialogue with African socio-cultural anthropology, theological reflection, and environmental ethics. Particular attention is given to key ethical themes such as harmony, justice, personhood, stewardship, and ubuntu, understood as a relational vision of life summarized in the expression, “I am because you are.” The article demonstrates that African religious worldviews offer important hermeneutical resources for reinterpreting the biblical doctrine of creation beyond exploitative anthropocentrism. It concludes that a constructive dialogue between Genesis 1–2 and African ethical traditions can contribute to a more contextually grounded eco-theology and encourage African religious communities to recover their vocation as responsible participants in the care of creation.